Enhancement of Ammonia Sensors Using In2O3 Sensing Electrode by Adjusting Particle Size and NiCo2O4 Reference Electrode. Issue 8 (1st August 2022) - Yang, Lin; Wu, Chunping; Zhang, Yiran; Xiao, Bang; Jiao, Anqi; Li, Ke; Chen, Ting; Zhan, Reggie; Lin, He
Abstract : A mixed potential ammonia sensor using In2 O3 sensing electrode was prepared, and its sensing performance was enhanced by adjusting particle size with calcination heating rate as well as the utilization of NiCo2 O4 reference electrode. It was found that the sensor with a calcination heating rate of 2 °C min −1 had the best performance, with a sensitivity of −61.27 mV decade −1 at 525 °C, and the TEM results showed that the average particle size was 70.36 nm. Furthermore, the sensor exhibited good stability against oxygen concentration fluctuation. The results also indicated that the mixed potential has a linear relationship with the logarithm of NH3 concentration, suggesting that the ammonia sensors in this study conform to the mixed potential theory. To address the issue that most ammonia sensors are susceptible to NO2 interference, NiCo2 O4 was used as reference electrode to replace the Pt reference electrode, which could greatly offset the response of NO2 and improve the sensors selectivity. In summary, the developed In2 O3 /YSZ/NiCo2 O4 sensor exhibited a great potential for NH3 monitoring in SCR systems.